Work-Family Conflict And Job Performance With Work Engagement As A Mediator (Study On Working Mothers) - Sandra Haryanto Gunawan; Yohanes Budiarto; P. Tommy Y. S. Suyasa (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to examine the mediating role of work engagement in the relationship between work family conflict and job performance. Work engagement is a positive work-related state of mind characterized by vigor, dedication and absorption. Work family conflict is a form of conflict between roles as professionals and roles in the family. Job performance is a description of tasks / work or work behavior as an employee in a company company. Participants in the study totaled 360 with the characteristics of women who are married (mothers), with school-age children, and work in a company. The measuring instrument used to measure work engagement is the Utrecht Work Engagement Scale 9 (Schaufeli et al, 2006). The measuring instrument used to measure work family conflict is the WFC & FWC Scale (Netemeyer et al., 1996). The measuring instrument used to measure job performance is the Individual Work Performance Questionnaire (IWPQ; Koopmans et al., 2014). Based on data analysis using the Moderated Regression Analysis (MRA) method, work engagement can mediate the relationship between work family conflict with task performance and contextual performance. The implication of the results of this study is that it can explain the relationship between work family conflict and job performance mediated by work engagement. In addition, the results of this study can be the basis for policy making to create a supportive environment for women to work optimally in the world of work.